STI Screening Uptake and Knowledge of STI Symptoms among Female Sex Workers Participating in a Community Randomized Trial in Peru - Kohler, Pamela K. (Int J STD AIDS, 2015)
This study aims to evaluate condom use, STI screening, and knowledge of STI symptoms among female sex workers (FSW) in Peru associated with sex work venue and a community randomized trial of STI control. One component of the Peru PREVEN intervention conducted mobile-team outreach to FSW to reduce STIs and increase condom use and access to government clinics for STI screening and evaluation. Prevalence ratios were calculated using multivariate Poisson regression models with robust standard errors, clustering by city. As-treated analyses were conducted to assess outcomes associated with reported exposure to the intervention. Care-seeking was more frequent in intervention communities, but differences were not statistically significant. FSW reporting exposure to the intervention had significantly higher likelihood of condom use, STI screening at public health clinics, and symptom recognition compared to those not exposed. Compared with street or bar-based FSW, brothel-based FSW reported significantly higher rates of condom use with last client, recent screening exams for STIs and HIV testing. Brothel-based FSW also more often reported knowledge of STIs and recognition of STI symptoms in women and in men. Interventions to promote STI-detection and prevention among FSW in Peru should consider structural or regulatory factors related to sex work venue.